The assessment of an intermittent high intensity running test - Psotta, R.; Blahus, P.; Cochrane, D. J.; Martin, A. J. (The Journal of Sports Medicine and Physical Fitness, 2005)
Aim: In multiple sprint sports the ability to perform repeated short duration bouts of maximal intensity exercise appears to be sport specific than the ability to perform prolonged continuous exercise or produce a single bout of exercise. However, previous studies have not verified a field test method with an appropriate intermittent anaerobic exercise pattern. The purpose of this study was to establish the reliability and validity of the Intermittent Anaerobic Running Test (IAnRT) primarily developed for soccer players. Methods: Twenty-nine trained male adolescent soccer players performed two separate 20 m sprints and the IAnRT on an indoor running track in each of two testing sessions separated by one recovery day. The IAnRT consisted of 10 20-m sprints with 20-s recovery periods between the sprints. Results: The mean running speed (Vm) and the speed at the beginning and the end of the IAnRT (V1+2, V9+10) confirmed good reliability. The relative mean speed index was the preferred indicator for assessing the ability to maintain short duration running performance during the intermittent exercise mode. Using confirmatory factor analysis the running performance of IAnRT was best explained by one general factor and one subfactor which consequently joined the general one from the 6th sprint (P=0.03, Bentler's d=0.99, RMSR=0.03). Conclusion: The IAnRT provided reliable and valid performance indices, which reflect the maximal anaerobic running power and capacity for repeated running sprints.